Intrusion detection system in cloud computing environment. (1st January 2012) - Dhage, Sudhir N.; Meshram, B.B.
In recent years, with the growing popularity of cloud computing, security in cloud has become an important issue. As 'prevention is better than cure', detecting and blocking an attack is better than responding to an attack after a system has been compromised. This paper proposes architecture capable of detecting intrusions, in a distributed cloud computing environment, and safeguarding it from possible security breaches. It deploys a separate instance of IDS for each user and uses a separate controller to manage the instances. IDS in this architecture can be signature-based as well as learning-based method.